Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 200257 by Calculusboy last updated on 16/Nov/23

Answered by witcher3 last updated on 16/Nov/23

ln^2 (x)+1=y⇒dy=2((ln(x))/x)  =∫y^2 tan^(−1) (y)dy  =(y^3 /3)tan^(−1) (y)−(1/3)∫(y^3 /(1+y^2 ))dy  =((y^3 tan^(−1) (y))/3)−(y^2 /6)+(1/6)ln(1+y^2 )+c∣

ln2(x)+1=ydy=2ln(x)x=y2tan1(y)dy=y33tan1(y)13y31+y2dy=y3tan1(y)3y26+16ln(1+y2)+c

Commented by Calculusboy last updated on 16/Nov/23

thanks sir

thankssir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com